2017
DOI: 10.1002/bjs.10475
|View full text |Cite
|
Sign up to set email alerts
|

Timing of completion lymphadenectomy after positive sentinel node biopsy in patients with melanoma

Abstract: The time interval between diagnosis of melanoma and CLND did not influence CLND tumour load, DFS or MSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Furthermore, the question, whether removing only the SLN is sufficient for disease control, is open. Previous studies showed that only 11.5–18.8% of patients undergoing CLND due to positive SLN have further positive lymph nodes . This supports the hypothesis that performing an SLNB ensures disease control.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the question, whether removing only the SLN is sufficient for disease control, is open. Previous studies showed that only 11.5–18.8% of patients undergoing CLND due to positive SLN have further positive lymph nodes . This supports the hypothesis that performing an SLNB ensures disease control.…”
Section: Discussionsupporting
confidence: 71%
“…Only patients with positive SLNB underwent CLND. Interestingly, studies showed that over 80% of patients who underwent CLND did not have any further positive lymph nodes . Additionally, recent randomized multicenter trials have suggested that performing a CLND does not significantly improve melanoma‐specific survival (MSS) but can only improve progression‐free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, details of complications were not available for all patients in the present series, so this aspect could not be evaluated. The timing of CLND after diagnosis of melanoma was not assessed in this study, but it has been demonstrated recently that this does not seem to influence tumour load, DFS or MSS.…”
Section: Discussionmentioning
confidence: 99%
“…CLND did not influence CLND tumour load, DFS or MSS, which is in line with our results. 9 However, these studies need to be viewed in light of the changing landscape in managing patients with CM with micrometastases in the SLN, especially with respect to immune and targeted therapies. 24,25 Nonetheless, our study contributes robust evidence that the outcome of patients with CM is not affected by the timing of surgical procedures such as SLNB and CLND.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervals reported vary greatly between different datasets, and most studies state a time delay to SLNB after primary resection of at least 30 days or even longer. [6][7][8][9][10][11][12][13][14][15][16] By contrast, we set out to investigate whether patients benefit from keeping the time span between primary resection and SLNB or between SLNB and complete lymph node dissection (CLND) as short as possible. To do so, procedures taking place ≤ 7 days after primary resection or SLNB were defined as very early (VE)-SLNB and -CLND, respectively.…”
Section: Introductionmentioning
confidence: 99%